Encyclopaedia of geographical science and environment - Ravi, Mishra (New Delhi, India : Anmol Publications Pvt. Ltd., 2001)
Vol.1. Geological environment -- Vol.2. Polar environment : issues and challenges -- Vol.3. Freshwater environment -- Vol.4. Marine environment -- Vol.5. Marine environment II